ANALISIS KESULITAN BELAJAR DAN FAKTOR YANG MEMPENGARUHI SISWA PADA MATA PELAJARAN EKONOMI - Multisari Fatra (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2016)
The research aims to analyze the contribution of learning difficulties and its effect on student learning outcomes. Research using quantitative descriptive approach with mixed method design. A population that is 70 respondents, with the withdrawal of samples using a purposive sampling technique i.e. students who have learning difficulties with a value below the KKM. Data collection techniques using documentation and question form. Documentation used to analyze about learning difficulties, While the now used to analyse factors affecting learning difficulties. Data analysis using regression analysis and linear grain problem compounds on SPSS. The results showed that the basic competencies that are difficult for students of class X, that is the concept of economic science, problems of Economics, behavioral economics and market equilibrium. As for Class XI regarding national income, growth and economic development, Regional Government Budget and The Indonesian Budget, and fiscal and monetary policies; (2) factors that influence the learning difficulties including learning interest of 5.763; motivation of 2.676; family environment of 3,349; and the school environment of 2.756; and those factors contribute to a negative with sig < 0.05, which means the smaller the factors influencing then the greater the learning difficulties of students, Instead the bigger factors influencing the students ' learning difficulties, small.